Childhood trauma and bullying-victimization as an explanation for differences in mental disorders by sexual orientation. (May 2021) - Baams, Laura; ten Have, Margreet; de Graaf, Ron; de Jonge, Peter
Abstract: Sexual minority individuals are more likely to have mental disorders, including mood, anxiety, and substance use disorders, compared to heterosexual individuals. Whether experiencing trauma or bullying-victimization during childhood explains these differences is currently unclear. We used a psychiatric epidemiological general population-based study to assess whether childhood trauma severity and bullying-victimization before age 16 explains the difference by sexual attraction in mental disorders. Data from the Netherlands Mental Health Survey and Incidence Study-2 (NEMESIS-2; N = 6392) were used to examine (1) whether same/both-sex attraction and predominantly other-sex attraction is linked to self-reports of childhood trauma (types and severity) and bullying-victimization, and (2) whether these experiences explain differences between these groups in lifetime and 12-month prevalence of DSM-IV disorders assessed by the Composite International Diagnostic Interview 3.0. Same/both-sex attracted individuals reported a higher childhood trauma severity score compared to exclusively other-sex attracted individuals ( B = 0.93, SE = 0.20, p < .001), and were more likely to report bullying-victimization ( OR = 2.51 95%CI[1.68, 3.74]). DSM-IV disorders were more prevalent among same/both-sex attracted individuals than among exclusively other-sex attracted individuals ( OR s ranged from 1.57 to 4.68). There were no differences in DSM-IV disorders for predominantly other-sex attracted individuals. Childhood trauma severity explained between 9.0% and 57.0% of significant indirect associations between same/both-sex attraction and DSM-IV disorders. Sexual minority individuals experience more types of, and more severe childhood trauma, and are more likely to experience bullying-victimization. These negative experiences partly explained disparities in mental disorders.